The Relevance of Traditional Martial Knowledge (Ilmu Kanuragan) in Strengthening Character Education in Pesantren - Imam Sofiyan; Imron Arifin (Journal Of Islamic Education And Pesantren, 2024)
Rapid social change in the contemporary era poses serious challenges to the strengthening of students’ character education, particularly in relation to discipline, self-control, perseverance, and moral responsibility. As a traditional Islamic educational institution, pesantren hold strategic potential to address these challenges through education grounded in lived traditions. This study aims to examine the relevance of kanuragan practices in strengthening character education among students at Pondok Pesantren Lirboyo Kediri. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, participant observation, and document analysis. Data analysis was conducted interactively with an emphasis on source and method triangulation. The findings indicate that kanuragan functions as a form of character education rooted in social praxis rather than merely as a physical or extracurricular activity. Values such as discipline, self-regulation, perseverance, responsibility, and ethical courage are internalized through structured training, authority relations based on moral exemplarity, and collective habituation within the pesantren’s daily life. A theory-driven discussion drawing on critical theory and Islamic educational perspectives demonstrates that kanuragan operates as an emancipatory educational space aligned with the principles of tarbiyah, adab, and habituation in the pesantren tradition. This study concludes that kanuragan possesses strong pedagogical as well as normative-theological relevance as a praxis-based model of contemporary Islamic character education grounded in students’ lived experience.